Improving the Quality of Islamic Religious Learning through the Implementation of Outdoor Learning - Baderiah, Baderiah; Mawardi, Mawardi (Journal of Indonesian Islamic Studies, 2025)
This research is field research in the form of descriptive qualitative, which analyzes the data in-depth, not based on numbers in analyzing the data. The data sources in this study are divided into two, namely primary data sources and secondary data sources. The objects of this study were 26 people consisting of the principal, 21 students, and four teachers of Islamic religious education at SMP Lestari, Belopa District, Luwu Regency. In collecting data, the author uses library research and field research methods. Data analysis is the process of arranging data sequences, organizing them into patterns, categories, and descriptions of basic units. The research results are: 1) Application of Outdoor Learning in Improving the Quality of Islamic Religious Education at SMP Lestari, Belopa District, Luwu Regency includes: a. Curriculum Management, b. Student Management, c. Learning Evaluation. 2) Factors that Inhibit Outdoor Learning in Improving the Quality of Islamic Religious Education at SMP Lestari, Belopa District, Luwu Regency and Solutions to Overcome it, namely: a. Limited facilities and infrastructure b. Lack of support from parents c. Lack of skilled and competent teachers in their fields.